Catastrophic loss of tropical seagrass habitats at the Cocos (Keeling) Islands due to multiple stressors. (September 2021) - Buckee, Joanna; Hetzel, Yasha; Nyegaard, Marianne; Evans, Scott; Whiting, Scott; Scott, Sarah; Ayvazian, Suzanne; van Keulen, Mike; Verduin, Jennifer
Abstract: Seagrass habitats at the Cocos (Keeling) Islands (CKI), a remote atoll in the Indian Ocean, have suffered a catastrophic decline over the last decade. Seagrass monitoring (1996–2020) in relation to dredging and coastal development works (2009 to 2011) provide a historical baseline, and document the decline of mixed tropical seagrass Thalassia hemprichii and macroalgal (predominantly Caulerpa spp.) beds over a decadal scale time series. Attribution of loss to coastal development is confounded by lagoon-wide die-off events in 2007, 2009 and 2012 and high air and water temperatures from 2009 to 2016, with evidence of broad scale changes, visible in satellite imagery between 2006 and 2018. We conclude that up to 80% of seagrass habitats in the CKI lagoon ( 1200 ha) have been lost due to multiple stressors including episodic die-off events related to high temperatures and calm conditions, and loss due to sediment disturbance and increased turbidity. Grazing pressure from the resident green sea turtles ( Chelonia mydas ) may have also exacerbated the loss of seagrass, which in turn poses a dire threat to their ongoing health and survival. This study highlights the fragility of tropical seagrass habitats and the cascading effect of system imbalance as a result of anthropogenic pressures and climate drivers. Although small in comparison to global estimates, the loss of seagrass habitats at CKI could change the entire ecosystem of a remote atoll. Due to the significance of the Thalassia beds for coastal stability, as food for an isolated population of green sea turtles and as a fish nursery, rehabilitation efforts are warranted. Graphical abstract: Unlabelled Image Highlights: 1200 ha (80%) of tropical seagrass has been lost at the Cocos (Keeling) Islands. Loss is attributed to multiple coastal development and climate-related stressors. Numerous lagoon die-off and thermal stress events are documented over recent decades. Sea turtle overgrazing is also implicated in seagrass loss. Turbidity-related impacts from coastal development are ongoing.